STRATEGI UNTUK MENJAGA KONSISTENSI DAN AKURASI DATA DALAM PENGAMBILAN KEPUTUSAN - Nanda muzahra; Muhammad Irwan Padli Nasution (JURNAL ILMIAH NUSANTARA, 2025)
In an increasingly integrated digital era, data-driven decision-making has become one of the crucial aspects of organizational management. However, this heavily depends on the quality of the available data, particularly in terms of consistency and accuracy. Data discrepancies or errors can lead to inaccurate decisions and may negatively impact both operational activities and long-term strategies. This study aims to examine various strategies that organizations can implement to maintain data consistency and accuracy within management information systems, such as data format standardization, data validation and verification, system integration, as well as regular auditing and data cleansing. By applying these approaches, organizations can enhance the reliability of the information used in decision-making processes, resulting in more accurate, efficient, and accountable decisions.